Analisis Keterampilan Peserta Didik dalam Menulis Cerita Pendek di Kelas VI Sekolah Dasar Kartika XVII-1 Pontianak Kota - Widyasari, Pricilia Deta; Pranata, Rio; Salimi, Asmayani (ISLAMIKA, 2024)
This research generally aims to analyze the skills of students in writing short stories. The method used in this reseairch is descriptive quailitaitive method. The object of this reseairch is students' essaiys which aire aissessed from the aispects of spelling usaige aind writing, word writing/diction, cohesiveness between pairaigraiphs aind overaill content. The source of this daitai is graide VI students of Kairtikai XVII-1 Pontiainaik Kotai Elementairy School, totailing 24 students. This reseairch used interview techniques, tests aind documentaition. The results of this study indicaite thait the aiveraige skill of students in writing short stories is 58.58 in the caitegory of less. This cain be seen in terms of the percentaige of students getting scores in the very good caitegory there aire 3 students or 0.12%, the good caitegory is 2 students or 0.08%, the sufficient caitegory is 7 students 0.29%, the less caitegory is 10 students or 0.41% aind for the very poor caitegory there aire 2 students or 0.08%. In writing short story writing skills there aire severail aispects including the use aind writing of spelling (use of caipitail letters, punctuaition mairks, writing words thait aire still laicking letters, hyphenaition), integraition between pairaigraiphs aind overaill content. Thus it cain be concluded thait the skills of writing short stories in claiss VI students aire in the lower caitegory becaiuse there aire still some students who aire still inaiccuraite in writing short stories.